New World species of the genus Calliscelio Ashmead (Hymenoptera, Platygastridae, Scelioninae) - Chen, Hua-yan (Zookeys, 2017)
Abstract. The genus Calliscelio Ashmead is presumed to be a diverse group of parasitoids of the eggs of crickets (Orthoptera: Gryllidae). A least one species has been found to be an important factor in depressing cricket pest populations. The New World species of Calliscelio are revised. Forty-two species are recognized, 3 are redescribed: Calliscelio bisulcatus (Kieffer), Calliscelio laticinctus Ashmead, Calliscelio rubriclavus (Ashmead), comb. n.; and 38 are described as new: Calliscelio absconditum Chen & Johnson, sp. n., Calliscelio absum Chen & Johnson, sp. n., Calliscelio alcoa Chen & Masner, sp. n., Calliscelio amadoi Chen & Johnson, sp. n., Calliscelio armila Chen & Masner, sp. n., Calliscelio bidens Chen & Masner, sp. n., Calliscelio brachys Chen & Johnson, sp. n., Calliscelio brevinotaulus Chen & Johnson, sp. n., Calliscelio brevitas Chen & Johnson, sp. n., Calliscelio carinigena Chen & Johnson, sp. n., Calliscelio crater Chen & Johnson, sp. n., Calliscelio crena Chen & Johnson, sp. n., Calliscelio eboris Chen & Johnson, sp. n., Calliscelio extenuatus Chen & Johnson, sp. n., Calliscelio flavicauda Chen & Johnson, sp. n., Calliscelio foveolatus Chen & Johnson, sp. n., Calliscelio gatineau Chen & Johnson, sp. n., Calliscelio glaber Chen & Masner, sp. n., Calliscelio granulatus Chen & Masner, sp. n., Calliscelio latifrons Chen & Johnson, sp. n., Calliscelio levis Chen & Johnson, sp. n., Calliscelio longius Chen & Johnson, sp. n., Calliscelio magnificus Chen & Masner, sp. n., Calliscelio migma Chen & Johnson, sp. n., Calliscelio minutia Chen & Johnson, sp. n., Calliscelio paraglaber Chen & Johnson, sp. n., Calliscelio pararemigio Chen & Masner, sp. n., Calliscelio prolixus Chen & Johnson, sp. n., Calliscelio punctatifrons Chen & Johnson, sp. n., Calliscelio remigio Chen & Masner, sp. n., Calliscelio ruga Chen & Johnson, sp. n., Calliscelio rugicoxa Chen & Masner, sp. n., Calliscelio sfina Chen & Johnson, sp. n., Calliscelio storea Chen & Johnson, sp. n., Calliscelio suni Chen & Johnson, sp. n., Calliscelio telum Chen & Johnson, sp. n., Calliscelio torqueo Chen & Johnson, sp. n., Calliscelio virga Chen & Johnson, sp. n. Four species are treated as junior synonyms of Calliscelio rubriclavus (Ashmead): Anteris nigriceps Ashmead, syn. n., Caloteleia marlattii Ashmead, syn. n., Caloteleia grenadensis Ashmead, syn. n., and Macroteleia ruskini Girault, syn. n.